Effect of preparation method on MnOx-CeO2 catalysts for NO oxidation - 崔明山 李渊 王欣全 王军 沈美庆 (Journal of rare earths, 2013)
The NO oxidation reaction was studied over MnOx-CeO2 catalysts prepared by co-precipitation, impregnation and mechanical mixing method, respectively. It was found that the co-precipitation was the most active and a 60% NO conversion was achieved at 250 oC. X-ray diffraction （XRD）, Brumauer-Emmett （BET）, H2-temperature programmed reduction （H2-TPR） and oxygen storage capacity （OSC） techniques were employed to characterize the physical and chemical properties of the catalysts. XRD results showed that amorphous MnOx or Mn-O-Ce solid solution existed in co-precipitation and impregnation prepared sample, while crystalline MnOx was found in mechanical mixing catalyst. A larger surface area was observed on co-precipitation prepared catalyst compared to those prepared by impregnation and mechanical mixing. The strong interaction between MnOx and CeO2 enhanced the reducibility of the oxides and increased the amount of Mn4＋ and activated oxygen, which are favorable for NO oxidation to NO2.